Entre a razão e a emoção: a busca pela adoção legal em Fortaleza-CE - Oliveira Filho, Antônio Diogo Cals de (2019)
The pursuit of legal adoption in Brazil is a process that has been involving representatives of the state and organized civil society for the past 30 years. From the promulgation of the Statute of the Child and Adolescent (ECA), in 1990, to the new adoptive law 13,509, 2017, major legal, doctrinal, symbolic and meaningful changes have come to fruiti on regarding the transfer of parenting in Brazil. This study aimed to understand how the search for legal adoption in the city of Fortaleza (CE) is structured through a participant observation in “Adoption Support Groups” (GAA). In this space I shared time with people who dedicate themselves to the adoptive theme in the State, get bogged down and affected in the search for the increase of adoptions in the city, especially in its legal sense, through the National Adoption Registry (CNA). After the insertion and participation in these places, I could understand how an adoptive social space has been formed in the city, involving parents and adopters, as well as representatives of the State and justice around disputes and partnerships. The central issue surrounding these actors is the quest to minimize waiting time in the adoption queue and to keep future adopters within the legal framework. Strategies and actions have been built to stimulate the delivery of children in adoption (voluntary / legal delivery), reduction of waiting time in the dismissals of family power (DPF), internalization of the ANC in the municipalities of the state and incursion to the media seeking disclosure of adoption. This strategy has produced adoptive powers, that is, an increase in the number of legal adoptions in the capital and of her municipalities of the state. To achieve this reality, GAA members use “emotion” and “foster experience” as a strategy for producing affections, while the state, in turn, rational-legal discourse aiming to insert and grow more and more. State interference through the ANC about the desire and search for suitors for children for adoption. Through clashes, splits and partnerships, the foster space in the city has grown in significance, but it is still facing unanswered challenge. The way so adoption have thus presented the difficulty of over coming historical dichotomies (legality-illegality / biological-affective / salvationism- social commitment), which have remained since their emergence as permanently in dispute constituent elements. In addition, the foster tripod (biological parents, foster parents, and foster children) has the interests constantly fluctuating. The relationship between them, mediated by the state, has shown, over time in Brazil, a tendency towards implementing laws that seek to encourage adoption, reduce the time of FPD and curb adoptions outside the queue. Nevertheless, the obstacles to the practice to be effective still running to structural dimensions of Brazil’s society, generating in the individuals who enter the adoptive system, distinct feelings ranging from frustration to militancy for the adoptive cause.